Evaluación del potencial natural de los paisajes para la actividad agropecuaria en el ejemplo del municipio de Yaguajay (provincia Sancti-Spiritus, Cuba) - Arceo Kindelán, Sara; Salinas Chávez, Eduardo (Geographicalia, 2017)
This article tries to show the advantages of the studies of integrated landscape and the determination of their natural resources in territorial management in Cuba.
Keywords: Natural resources; management; integrated landscape